Sfingolipidi bioattivi e loro ruolo nell'azione biologica di fattori di crescita e citochine - Bernacchioni, Caterina (Premio Tesi di Dottorato, 2012)
This book gives an analysis of the role of the bioactive sphingolipids sphingosine-1-phosphate (S1P) and ceramide 1-phosphate (C1P) in the skeletal muscle. The enzyme that produces S1P, sphingosine kinase 1 (SK1) has proved crucial in the biological action of growth factors and cytokines involved in the inflammatory process that follows muscular damage. Indeed, in myoblasts the cytokine TGFβ exercises its fibrotic action through induction of the SK1/S1P axis. Furthermore, the PDGF growth factor, positive regulator of proliferation and motility, activates the enzyme SK1 and the transactivation of S1P1 inhibits the proliferation and induces the migration induced by the growth factor. Finally, the mitogenic role of C1P in myoblasts has been identified, characterizing the signalling pathways involved.